Reception characteristics investigation and measurement of capacitive micromachined ultrasonic transducer. Issue 2 (12th September 2019) - Wang, Hongliang; Wang, Xiangjun; He, Changde; Xue, Chenyang
Abstract : Purpose: As a new type of ultrasonic transducer with significant advantages, capacitive micromachined ultrasonic transducer (CMUT) has good application prospect. The reception characteristic of the CMUT is one of the important factors determining the application effect. This paper aims to study the reception characteristics of CMUT. Design/methodology/approach: In this paper, the state equation is deduced and the analysis model is established in SIMULINK environment based on the lumped parameter system model of the CMUT cell. Based on this analysis model, the influencing factors of CMUT reception characteristics are studied and investigated, and the time-domain and frequency-domain characteristics are investigated in detail. Findings: The analysis results show that parameters directly affect the reception characteristics of the CMUT, such as direct current (DC) bias voltage, input sound pressure amplitude and frequency. At the same time, the measurement system is built and the reception characteristics are verified. Originality/value: This paper provides an effective method for rapid analyzing the reception characteristics of CMUT. These results provide an important theoretical basis and reference for further optimization of CMUT structure design, and lay a good foundation for the practical application measurement.